A simple approach to hybrid inorganic–organic step-growth hydrogels with scalable control of physicochemical properties and biodegradability1. Issue 12 (28th March 2015) - Alves, F.; Nischang, I.
<x xml:space="preserve">Abstract</x> We prepared new and scalable, hybrid inorganic–organic step-growth hydrogels with polyhedral oligomeric silsesquioxane (POSS) network knot construction elements and hydrolytically degradable poly(ethylene glycol) (PEG) di-ester macromonomers by in situ radical-mediated thiol–ene photopolymerization.